HUBUNGAN PENGETAHUAN REMAJA SANTRIWATI TENTANG PERINEAL HYGIENE DENGAN PERILAKU PENCEGAHAN KEPUTIHAN (FLOUR ALBUS) DI PONDOK PESANTREN DAARUL MUKHTARIN - Muftadiyah, Ayu; Zubairi, Ahmad (Nusantara Hasana Journal, 2022)
Women's reproductive health has become a health issue that must be considered, especially in the teenage years. Various reproductive health problems can occur in adolescence, one of which is due to lack of attention and knowledge related to reproductive health. Problems with reproductive organs in adolescent often occur in developing countries, such as Indonesia. Based on reproductive health research data, 75% of women have experienced vaginal discharge at least once in their lives. In Europe, the incidence of vaginal discharge is only 25%, while in Indonesia 50% of women experience vaginal discharge. The incidence of vaginal discharge continues to increase very year reaching 70%. The purpose of this research was to determine the relationship between knowledge of perineal hygiene for the prevention of vaginal discharge (flour albus) in Daarul Mukhtarin Islamic Boarding School. The design  of this research used decrip analytic withdesign cross sectional. The sample used random sampling with the number of respondents 80 people. Data analysis used univariate and bivariate, namely chi square. The results of the research the most  perineal hygiene knowledge is good (86.3%), good prevention (87.5%). The results of thetest chi square have a relationship between knowledge of perineal hygiene for the prevention of leuchorrea (flour albus) with (p-value = 0.000). The conclusion of this reseach is that there is a relationship between the knowledge of adolescent female students about  perineal hygiene  and the behavior of preventing vaginal discharge (fluor albus) at Daarul Mukhtarin Islamic Boarding School.